2018
DOI: 10.1021/acs.chemrestox.8b00129
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Molecular Toxicity Profile of Dental Bioceramics in Embryonic Zebrafish (Danio rerio)

Abstract: The investigation of the biocompatibility of potential and commercially available dental material is a major challenge in dental science. This study demonstrates that the zebrafish model is a novel in vivo model for investigating the biocompatibility of dental materials. Two commercially available dental materials, mineral trioxide aggregate (MTA) and Biodentine, were assessed for their biocompatibility. The biocompatibility analysis was performed in embryonic zebrafish with the help of standard toxicity assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…These results are in line with those reported by Makkar et al [45] who used the Zebra sh model to study the biocompatibility of two dental bioceramics, one of which is the mineral trioxide aggregate (MTA) composed mainly of inorganic elements containing calcium. The eluates of MTA contain silicates, aluminates and calcium oxides, which facilitated the increase in abnormal metabolic activity in embryonic cells, causing a percentage of embryonic deaths from oxidative stress and cellular apoptosis.…”
Section: In Vivo Toxicity Assayssupporting
confidence: 91%
“…These results are in line with those reported by Makkar et al [45] who used the Zebra sh model to study the biocompatibility of two dental bioceramics, one of which is the mineral trioxide aggregate (MTA) composed mainly of inorganic elements containing calcium. The eluates of MTA contain silicates, aluminates and calcium oxides, which facilitated the increase in abnormal metabolic activity in embryonic cells, causing a percentage of embryonic deaths from oxidative stress and cellular apoptosis.…”
Section: In Vivo Toxicity Assayssupporting
confidence: 91%
“…This allows a densely cross-linked network formation which achieves its final properties, being able to withstand stresses resulting from forces applied in the oral cavity, resistance to degradation and prevention of monomer elution which raises toxicity concerns [ 34 , 46 ]. Materials which aspire biomimetism should limit their toxicity, which, in this case, can be achieved by reducing the free-monomer elution owing to incomplete polymerisation [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biocompatibility of a compound depends on its cytotoxic effect that can be inferred by assessing its morphological, cellular, metabolic, and molecular changes due to their exposure to live models 15 . Developmental deformities and oxidative stress are such phenomena that are widely assessed to study growth and metabolic dynamics 34 . In vivo developmental analyses in the present study showed that Chaga mushroom polysaccharide extract did not show any significant developmental changes in the exposed zebrafish embryos compared to control.…”
Section: Discussionmentioning
confidence: 99%